Resposta germinativa de sementes de Libidibia ferrea Martius submetidas a fatores abióticos - Dantas, Joelma Medeiros (Universidade Federal Rural do Semi-Árido, 2015)
The L. ferrea is a plant in the Fabaceae family-Caesalpinoidae, commonly known jucá or ironwood is commonly found in the Caatinga of northeastern Brazil. The study investigated the germination response L. ferrea seeds in function of temperature and variation of osmotic potential.The research was conducted in the Biotechnology Laboratory at the Universidade Federal do Semi-Árido (UFERSA), Mossoró-RN. The work was divided into two experiments. In the first experiment was the curve of absorption of the seeds in different EC (Electrical Conductivity) 0 dSm-1 (control), 5dSm-1, 10 dSm-1, 15 dSm-1, 20 dSm-1 at constant temperatures of 15, 22, 27, 32 and 40°C. In the second experiment we observed the effects of osmotic potential (0, 5, 10, 15 and 20 dSm-1) and constant temperatures (15, 22, 27, 32, and 40°C), seed germination. The conclusion of this study that the EC influence the absorption of water by jucá seeds. At higher temperatures the absorption is faster, but with increased absorption EC decreases. The best germination was found at 27°C. The EC influenced seed germination, IVG and length of jucá seedlings as they increased the concentration of salts
Germinal response Libidibia seeds ferrea Martius subjected to abiotic factors
Keywords: Germination; Jucá seeds; Electric conductivity; Salinity; Caatinga - Northeast Brazil; Germinação; Sementes de jucá; Condutividade elétrica; Salinidade; Caatinga - Nordeste brasileiro; CIENCIAS BIOLOGICAS::ECOLOGIA